Socio-Demographic Profiling of Alleged Perpetrators of Sexual Offence Brought for Medico-Legal Examination at a Tertiary Center, Dhulikhel - Khan , Abdul Sami; Karki , Anish; Pathak , Shikha; Paudel, Anish (Med Phoenix, 2025)
Introduction: Sexual assault is defined as any sexual act committed by one (or more) person against another person without their consent. Sexual assault remains one of the most despicable and cruel crimes that persists in our country. Materials and Methods: The study was a retrospective cross-sectional study of medico-legal reports of alleged perpetrators examined in between the period of 13 April 2020-12 April 2024 presenting to the Department of Forensic Medicine and Toxicology, Dhulikhel Hospital. The cases will be assessed for the statistics regarding the demography to age, marital status, address, clothes changed, body injury, genital injuries, bite marks, place of incidence, age gap and relationship with the victim. Results: A total of 129 alleged perpetrators brought for medico-legal examination in the forensic medicine department were included in this study. Majority of the perpetrators belonged to age group between 21 years to 30 years amounting to 34.8% of the cases. Maximum alleged perpetrators were married (58.1%). 34.8% of the alleged perpetrators belonged to O positive blood group. Only 12 out of 129 alleged perpetrators (9.3%) accepted the offence. 53.4% had changed their clothes and 42.6% of them had taken bath after the offence. Most of the incidents (27.1%) occurred in victim's house followed by perpetrator's house (19.4%). The age gap with the victim was 0-10 years in 47.3% cases. Most of the alleged perpetrators (58.1%) were known to the victim. Conclusion: Most of the married young men were involved in sexual offences. Most of the alleged perpetrators had changed their clothes when brought for examination which is a major challenge in identification of the culprit. Most of the alleged perpetrators were acquaintances. Majority of the assailants were from Panchkhal. The research results could provide useful basic data and would be advantageous for policymakers and program organizers to raise awareness among the public.